التربية القرآنية للإنسان والدفع الحضاري: "عقيدة تكريم الإنسان وتضميناتها التربوية عند عبد المجيد النجار أنموذجاً" - هجيرة شبلي (International Institute of Islamic Thought, 2019)
تتناول هذه الدراسة قضية التربية القرآنية للإنسان المسلم؛ بغية إعداده لممارسة مهمة الاستخلاف والتعمير في الأرض. وقد استخدم المفكر الإسلامي المعاصر عبدالمجيد النجار مصطلح عقيدة التكريم، التي تهدف إلى تعميق الإيمان والوعي لدى الإنسان المسلم؛ حول تفضيل الله سبحانه له على سائر المخلوقات، وتمكينه من تسخير الكون له من أجل أداء المهمة الوجودية التي كُلِّف بها. من هنا كان الهدف من التربية القرآنية أن تحدد غاية الوجود البشري، وتعزز عقيدة التكريم بتضميناتها التربوية وتمكن الإنسان من تجاوُز العوائق والتفاعل الإيجابي مع الكون. This study covers the issue of Qur'anic education of Muslims, in order to prepare them to perform the duty of vicegerency and building civilization on Earth. Abdul Majid al-Najjar, a contemporary Muslim thinker, calls this issue the doctrine of human dignity that deepens the Muslim's faith and awareness. This doctrine designates a human as a dignified being, over all creatures, in order to utilize nature and to execute his/her ontological duty. Methodology of Qur'anic education defines the purpose of human existence and promotes the doctrine of human dignity. This methodology has educational implications that enable humans to overcome obstacles and prepare them to interact positively with nature.